Comparison of reported physical illness and irrational beliefs of men and women in midlife - Mapilaparambil, Emilyn T. (Animo Repository, 1996)
This study investigates the relationship between the physical illness and the irrational beliefs of Filipino men and women in midlife. It also determines if there is a significant difference between the profile of men and women in terms of physical illness and their degree of adherence to irrational beliefs. Thirty men and thirty women with ages ranging from 35-45 years participated in this study. The Irrational Belief Tests (IBT) and the Illness Survey Questionnaire (ISQ) were used as instruments in this descriptive correlational research. For statistical analysis, means and standard deviations were computed in order to determine the profile of physical illness and irrational beliefs. Pearson r was used to investigate the relationship between the physical illness and the irrational beliefs. The t-test for independent samples was computed to determine the significant difference between the profiles of men and women in terms of physical illness and their degree of adherence to irrational beliefs. The results revealed that both male and female respondents at midlife were susceptible to physical illness. They had moderately high degree of adherence to each of the ten irrational beliefs. A significant relationship between physical illness and irrational beliefs especially those relating to problem avoidance, anxious overconcern, high self-expectations and perfectionism, was observed for men in midlife. On the other hand, no significant relationship was found for women. Irrational beliefs, especially those relating to demand for approval, blame proneness, dependency, and perfectionism, were some of the mediating variables of physical illness for women. Among midlifers, no gender difference was found in terms of susceptibility to physical illness and the degree of adherence to irrational beliefs. Thus, the findings were applicable to both sexes.